PENERAPAN METODE USABILITY UNTUK MENENTUKAN TINGKAT KEPUASAN PADA SISTEM MOBILE M-BANKING BRIMO - Haristina Putri, Maulida; Sanjaya, M. Rudi; Kurniawan, Dedy; Indah, Dwi Rosa (The Indonesian Journal of Computer Science, 2025)
This study aims to analyze the level of user satisfaction with the BRImo Mobile Banking application using the usability method.Research fokus includes usability aspects:learnability, efficiency, memorability, errors, and satisfaction. Data obtained through questionnaires distributed to 252 respondents in Palembang City.The results showed learnability had communalities of 0.599-0.703 and correlations of 0.432-0.514, while efficiency achieved communalities of 0.585-0.649 with correlations of 0.415-0.550.In contrast,errors had a significant negative impact,with a correlation of -0.352 to -0.488, indicating the more errors,the lower user satisfaction.Memorability shows communalities values between 0.511 to 0.663. BRImo application features, such as efficiency in transaction access speed (efficiency_2 and efficiency_3) which have a correlation of 0.498-0.550,as well as overall ease of access (learnability_5) with a correlation of 0.467,have a positive influence on user satisfaction. Technical issues such as bugs,crashes, and slow applications negatively impact user satisfaction,with errors_5 having low communalities of 0.445 and a significant negative correlation of -0.382,indicating technical errors strongly influence user